Exploring the Link between Vitamin D Levels and Bone Health: Insights into Osteopenia and Osteoporosis Among Postmenopausal Women in Basrah, Iraq: Mengeksplorasi Hubungan antara Kadar Vitamin D dan Kesehatan Tulang: Wawasan tentang Osteopenia dan Osteoporosis di Kalangan Wanita Pascamenopause di Basrah, Irak - Hussein, Mustafa Abd Almajeed; Ibrahim, Nawal Khalil (Indonesian Journal on Health Science and Medicine, 2024)
Although vitamin D is essential for bone metabolism, postmenopausal women frequently experience vitamin D insufficiency and shortage, which may have an impact on microarchticher, and bone mineral density (BMD). However, the results of previous research are inconsistent, and need more investigation for advanced research of extensive studies that are now available. Methods: 260 postmenopausal women age between (55-75) years old who were diagnosed with osteopenia and osteoporosis were included in this investigation. The parameter were gauged include serum 25,(OH) D level. Dual-energy X-ray absorptiometry (DXA) was used to diagnose BMD in all locations, including the lumbar spine, femoral neck, and whole hip. Using a generic linear model with body mass index and age adjustments, the relationships between serum 25,(OH) D levels and BMDs were examined. Results: There were significant differences of serum 25,(OH) D for the osteopenia group and also for the osteoporosis group in every patient that was part in this study. 25,(OH) D low levels were positively correlated with both pelvic and femur neck BMD in the osteoporosis group. Additionally, to the osteopenia cohort group, deficiency vitamin D scales were linked in neck femur and total hip BMD. The same patterns were noted in patients with osteoporosis (p < 0.05) and decrease levels of 25,(OH) D in those with lumbar spine BMD. Conclusions: Postmenopausal women with osteopenia and osteoporosis had a significant frequency of vitamin D deficiency and insufficiency, according to this study, which also examined the connections between vitamin D and BMD; the findings advance a more thorough comprehension of the potential effects of vitamin D on bone health. Highlights: Assess vitamin D's impact on BMD in postmenopausal women. Analyzed 260 women using serum 25(OH)D and DXA measurements. Vitamin D deficiency linked to lower BMD in spine and hip.. Keywords: Vitamin D, Osteoporosis, Osteopenia, Postmenopausal Women